2020
DOI: 10.2166/wst.2020.450
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric approach to the perspectives and challenges of membrane separation processes to remove emerging contaminants from water

Abstract: The presence of contaminants in water is concerning due to the potential impacts on human health and the environment, and ingested contaminants cause harm in various ways. The conventional water treatment systems are not efficient to remove these contaminants. Therefore, novel techniques and materials for the removal of contaminants are increasingly being developed. The separation process using modified membranes can remove these micropollutants; therefore, they have attracted significant research attention. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 156 publications
0
3
0
Order By: Relevance
“…NF is an intermediate process between RO and ultrafiltration (UF), and it can retain dissolved molecules with molar mass ranging from 200 to 1,000 g mol -1 and multivalent ions (Gomes et al, 2020). Many works have shown that the membrane separation process is efficient for the tertiary treatment of effluents (Cadore et al, 2020), including NF. A similar result was reported by Azaïs et al (2014) when they used NF for the separation of carbamazepine, and the rejection was 60%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NF is an intermediate process between RO and ultrafiltration (UF), and it can retain dissolved molecules with molar mass ranging from 200 to 1,000 g mol -1 and multivalent ions (Gomes et al, 2020). Many works have shown that the membrane separation process is efficient for the tertiary treatment of effluents (Cadore et al, 2020), including NF. A similar result was reported by Azaïs et al (2014) when they used NF for the separation of carbamazepine, and the rejection was 60%.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional water treatment is not efficient in removing or degrading emerging pollutants, therefore demanding studies and applications of complementary technologies (Cadore et al 2020). Thus, biological treatments, such as trickling filters or activated sludge, are mainly insufficient to remove a wide range of highly toxic contaminants, such as drugs, pesticides, and metals (Power et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation